The Triassic reptile Prolacerta in Antarctica. American Museum novitates - Colbert, Edwin Harris, 1905- (New York, N.Y. : American Museum of Natural History, 1987)
19 p. : ill. 26 cm. Includes bibliographical references (p. 18-19). "The prolacertid reptile, Prolacerta broomi, hitherto known from the Lystrosaurus Zone of the Middle Beaufort beds of South Africa, is described from specimens including two skulls with jaws, other fragments with skulls and jaws, and various postcranial elements, found in the Fremouw Formation of the Transantarctic Mountains. The Antarctic fossils represent individuals generally somewhat smaller than those known from South Africa, with slightly fewer teeth in the upper and lower jaws, and with other minor differences. These variations are, however, probably attributable to age differences and perhaps geographic separation rather than to any specific distinctions. A partial skeleton, including hind limbs and some caudal vertebrae of prolacertilian relationships, likewise would seem to represent an individual somewhat smaller than the South African species. The presence of Prolacerta broomi - in addition to a lydekkerinid amphibian Cryobatrachus kitchingi, the dicynodont reptiles Lystrosaurus murrayi, Lystrosaurus curvatus, Lystrosaurus mccaigi, and Myosaurus gracilis, the procolophonid Procolophon trigoniceps, and the theriodonts Thrinaxodon liorhinus and Ericiolacerta parva - corroborates the close relationships between Antarctica and South Africa and their probable connection during early Triassic time"--P. [1].